(3aVGFd YKeGf Hf YaGf (B( (3QVi Gddg Yfg (B)s - (3YHO Gddg Hf CMeO Hf eMeO Hf MfHd GdTjHGfj GdHZOGOj, CHh YHO GdQMef,J (B290 (3g` s ((3YHjO Gddg YeQ Hf YHO GdQMje Hf GdYLei s)
(3ChdgG (B:s
(3CNHQfG TjNfG GdEeGe GdYGde GdMGaX s
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B65 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B29s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B3 - (3U (B230 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs